A Janus Amyloid-like Nanofilm Inhibits Colorectal Cancer Postoperative Recurrence and Abdominal Adhesion via Synergistic Enzyme Cascade - Man Zhang; Junhao Kou; Zhenyi Song; Ling Qiu; Chunzhao Yang; Qi Xue (Nanomaterials)
Postoperative peritoneal adhesion and high recurrence rates are critical challenges in the clinical treatment of colorectal cancer. In this study, based on amyloid-like protein self-assembly technology, a novel Janus protein film was developed. The protein film encapsulates glucose oxidase (GOx) and catalase (CAT), which is named PTL@GC. Through a one-step method involving cysteine-reduced lysozyme-induced amyloid-like self-assembly, the film was co-loaded with GOx and CAT to achieve synergistic anti-adhesion and anti-tumor recurrence effects. The Janus film features a hydrophobic side that stably adheres to the intestinal surface without exogenous chemical modification and a hydrophilic side that prevents adhesion. The loaded GOx selectively induces disulfidptosis in SLC7A11-overexpressing tumor cells, while CAT degrades H2O2 to alleviate hypoxia and inhibit oxidative stress, significantly reducing adhesion-related fibrosis. The experimental results demonstrate that PTL@GC exhibited excellent mechanical properties, high enzyme activity retention (>90%), and controllable degradability (complete metabolism within 50 days). In animal models, PTL@GC reduced postoperative adhesion area by 22.77%, decreased local tumor burden to 28.42% of the control group, and achieved an inhibition rate of 58.49%, without inducing systemic toxicity. This study presents a biologically safe and functionally synergistic approach to addressing dual complications following colorectal cancer surgery, offering potential insights for future research on multifunctional Janus materials.